The Effect of Giving Red Ginger Oil On Pain After Iud Installation at Midwifery Independent Practice in Turen Malang Regency - Jayanti, Putri Agus Nur Dwi; Ilmiah, Widi Shofa; Wijayanti, Tut Rayani Aksohini (Universitas Malahayati, 2024)
ABSTRACT IUD installation pain is caused by a foreign body that enters the uterus, so to help the adaptation process, it is necessary to have treatment both pharmacologically and non-pharmacologically. The more frequent the pain that arises, the more recommended non-pharmacological treatment because it has a low risk. In post-IUD pain, there is complementary care in the form of essential oils. Essential oils often used are olive oil, peppermint oil, lavender oil, coconut oil, clove oil, and the latest red ginger oil. Complementary care can be done by giving Red Ginger Oil as a natural analgesic. The purpose of this study is to examine the impact of administering red ginger oil on post-IUD discomfort in a midwifery practice in Turen, Malang Regency. Experimental quantitative research using a one-group pre- and post-test design is what this study employs. The 18 people that filled out the survey were chosen using a quota system. The findings of the research were obtained three days after the controlled intervention, after the administration of Red Ginger Oil. Supplemental care, which posed less of a threat, was easily comprehended by patients. This research found that red ginger oil greatly alleviates uterine discomfort when administered topically. Keywords: IUD, Red Ginger Oil, Pain